Influence of physical training on erythrocyte concentrations of iron, phosphorus and magnesium - Marcos Maynar Mariño; Francisco Javier Grijota; Ignacio Bartolomé; Jesús Siquier-Coll; Victor Toro Román; Diego Muñoz (Taylor & Francis Group, 2020)
Background The present study aimed to determine changes occurring in the erythrocyte concentrations of Iron (Fe), Magnesium (Mg) and Phosphorous (P) of subjects with different levels of physical training living in the same area of Extremadura (Spain). Methods Thirty sedentary subjects (24.34 ± 3.02 years) without sports practice and a less active lifestyle, formed the control group (CG); 24 non-professional subjects (23.53 ± 1.85 years), who perform between 4 and 6 h/week of moderate sports practice without any performance objective and without following systematic training formed the group of subjects with a moderate level of training (MTG), and 22 professional cyclists (23.29 ± 2.73 years) at the beginning of their sports season, who performed more than 20 h/week of training, formed the high-level training group (HTG). Erythrocyte samples from all subjects were collected and frozen at − 80 °C until analysis. Erythrocyte analysis of Fe, Mg and P was performed by inductively coupled plasma mass spectrometry (ICP-MS). All results are expressed in μg/g Hb. Results The results showed that there were statistically significant lower concentrations of erythrocyte Fe, Mg and P in MTG and HTG than CG. All parameters (Fe, Mg and P concentrations in erythrocytes) correlated inversely with physical training. Conclusions Physical exercise produces a decrease in erythrocyte concentrations of Fe, Mg and P. This situation could cause alterations in the performance of athletes given the importance of these elements. For this reason, we recommend an erythrocyte control at the beginning, and during the training period, to avoid harmful deficits.